Economic analysis of the greenhouse effect: optimal abatement level and strategies for mitigation. (4th August 2014) - Adger, Neil; Fankhauser, Samuel
The economic analysis of global warming involves identifying and quantifying in economic terms the impacts of global warming and the abatement costs of greenhouse gas emissions. At the global level, countries will act strategically depending on their perceived costs and impacts. This is simulated through a global model of costs and damage of global warming. At the local level, the impacts of global warming are effectively exogenous to the decision problem. This is illustrated by a case study of mitigation options in the face of climate–induced sea–level rise in East Anglia, UK. Both cases result in recommendations for precautionary action in the face of uncertainty as to the future potential damage of global warming.